Interdisciplinary education in the context of protection of water resources: A case study in Vietnam - Dung, Tang Minh; Nga, Nguyen Thi; Thanh, Lam Thien (Journal of Education and e-Learning Research, 2023)
The incorporation of interdisciplinary education, a topic of significant global interest, is increasingly being recognized as a key aspect of educational innovation in Vietnam. This recognition extends to several fields, including STEM (Science, Technology, Engineering, and Mathematics) education.This research aims to design and implement a STEM situation associated with the context of water protection in Vietnam for 10th-grade students in which students mobilize the knowledge of Physics (specific gravity, Archimedes’ principle) and Mathematics (volume) to design a salinometer. This device measures the salinity of the water. The research methodology is based on the observed increase in saline levels in the coastal regions of Vietnam in recent years, which has had a substantial impact on agriculture and the livelihoods of millions of people. This methodology aims to provide realistic scenarios for students to address and resolve these problems. A total of forty students in the 10th grade were involved in a teaching situation that consisted of five distinct phases. Forty 10th-grade students participated in a teaching situation conducted in five phases. The results showed that the situation helped students strengthen and connect their physics and mathematics knowledge, create a vibrant learning atmosphere, enhance communication, and develop problem-solving competency. Furthermore, the teaching situation also needs to be revised regarding the measurement practices of Vietnamese students. The situation contributes to educating students’ awareness of current events, protecting Vietnamese water resources, and the importance of sustainable development. In addition, we can use the same teaching process as in this research to develop other STEM teaching situations.